Molecular dynamics simulation of photodissociation of carbon monoxide from hemoglobin. - Henry, E R (1985)
A molecular dynamics simulation of the photodissociation of carbon monoxide from the alpha subunit of hemoglobin is described. To initiate photodissociation, trajectories of the liganded molecule were interrupted, the iron-carbon monoxide bond was broken, and the parameters of the iron-nitrogen bonds were simultaneously altered to produce a deoxyheme conformation. Heme potential functions were used that reproduce the energies and forces for the iron out-of-plane motion obtained from quantum mechanical calculations. The effect of the protein on the rate and extent of the displacement of the iron from the porphyrin plane was assessed by comparing the results with those obtained for an isolated complex of heme with imidazole and carbon monoxide. The half-time for the displacement of the iron from the porphyrin plane was found to be 50-150 fs for both the protein and the isolated complex. These results support the interpretation of optical absorption studies using 250-fs laser pulses that the iron is displaced from the porphyrin plane within 350 fs in both hemoglobin and a free heme complex in solution.